BRIDGING LAW AND PRACTICE: REFRAMING DISABILITY RIGHTS IN INDONESIAN FAITH-BASED CHILD PROTECTION THROUGH MAQASID AL-SHARIAH - Fadhilah, Nur; Nurhidayah, Siti; Sa'adah, Mazro'atus (Faculty of Law, Universitas Tanjungpura, 2026)
Abstract This study examines the implementation of disability protection within a faith-based institution in Bananul Amanah Madiun Foundation, addressing a critical gap between normative legal frameworks and their practical realization in institutional care settings. It asks how disability laws are operationalized in practice and how maqāṣid al-sharīʿah can strengthen disability rights analysis beyond formal legal compliance. Using a qualitative socio-legal case study, the research draws on fieldwork conducted over three months involving eighteen participants, including administrators, caregivers, educators, parents, and children, supported by observations and institutional document analysis. The findings reveal a hybrid and adaptive model in which legal norms, religious values, and institutional practices interact dynamically. While the institution demonstrates strong commitment to safeguarding life, dignity, and basic welfare, implementation remains partial due to structural constraints such as limited resources, weak coordination, and insufficient professional capacity. The analysis shows that maqāṣid al-sharīʿah provides a systematic ethical framework that deepens rights-based evaluation by linking protection of life, intellect, and dignity to concrete institutional practices. This study contributes theoretically by integrating maqāṣid with socio-legal analysis to explain the gap between law and practice in disability protection. It implies that strengthening inclusive welfare systems in Muslim-majority contexts requires combining normative frameworks with institutional capacity building and integrated governance strategies. Abstrak Penelitian ini mengkaji implementasi perlindungan penyandang disabilitas pada institusi berbasis keagamaan, Yayasan Bananul Amanah Madiun, dengan menyoroti kesenjangan kritis antara kerangka hukum normatif dan realisasinya dalam praktik layanan kelembagaan. Pertanyaan penelitian ini meliputi: bagaimana regulasi disabilitas dioperasionalisasikan dalam praktik serta bagaimana maqāṣid al-sharīʿah dapat memperkuat analisis hak-hak disabilitas melampaui kepatuhan hukum formal. Dengan menggunakan pendekatan studi kasus sosio-legal kualitatif, penelitian ini didasarkan pada kerja lapangan selama tiga bulan yang melibatkan delapan belas partisipan, termasuk pengelola, pengasuh, pendidik, orang tua, dan anak-anak, yang didukung oleh observasi serta analisis dokumen institusi. Temuan penelitian menunjukkan adanya model hibrida dan adaptif, di mana norma hukum, nilai-nilai keagamaan, dan praktik kelembagaan berinteraksi secara dinamis. Meskipun institusi menunjukkan komitmen yang kuat dalam melindungi kehidupan, martabat, dan kesejahteraan dasar, implementasinya masih bersifat parsial akibat kendala struktural seperti keterbatasan sumber daya, lemahnya koordinasi, dan kurangnya kapasitas profesional. Analisis ini menunjukkan bahwa maqāṣid al-sharīʿah menyediakan kerangka etis yang sistematis untuk memperdalam evaluasi berbasis hak dengan mengaitkan perlindungan jiwa, akal, dan martabat dengan praktik kelembagaan konkret. Penelitian ini memberikan kontribusi teoretis melalui integrasi maqāṣid dengan analisis sosio-legal untuk menjelaskan kesenjangan antara hukum dan praktik dalam perlindungan disabilitas. Implikasinya, penguatan sistem kesejahteraan inklusif di konteks negara mayoritas Muslim memerlukan integrasi antara kerangka normatif, penguatan kapasitas kelembagaan, dan strategi tata kelola yang terkoordinasi.